1999
DOI: 10.1038/sj.bjc.6690293
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization detects many recurrent imbalances in central nervous system primitive neuroectodermal tumours in children

Abstract: Summary A series of 23 children with primitive neuroectodermal tumours (PNET) were analysed with comparative genomic hybridization (CGH). Multiple chromosomal imbalances have been detected in 20 patients. The most frequently involved chromosome was chromosome 17, with a gain of 17q (11 cases) and loss of 17p (eight cases). Further recurrent copy number changes were detected. Extra copies of chromosome 7 were present in nine patients and gains of 1q were detected in six patients. A moderate genomic amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
30
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 21 publications
10
30
0
Order By: Relevance
“…Using more sophisticated and advanced techniques such as CGH to profile a panel of 27 primary MB (Reardon et al 1997) revealed frequent loss of 10q, 11, 16q, 17p, and 8p as well as recurrent gains of chromosomes 7, and 17q. These losses and gains were also confirmed by other techniques, such as G-banding, SKY and FISH (Aldosari et al 2002;Avet-Loiseau et al 1999 ;Bayani et al 2000;Eberhart et al 2002;Gilhuis et al 2000). Array CGH of 47 MB (Speicher and Carter 2005) showed gain of 17q, 7, and 1q and loss of 17p, 11p,10q and 8.…”
Section: Chromosomal Aberration and Its Corroletion To Clinicohistopasupporting
confidence: 54%
“…Using more sophisticated and advanced techniques such as CGH to profile a panel of 27 primary MB (Reardon et al 1997) revealed frequent loss of 10q, 11, 16q, 17p, and 8p as well as recurrent gains of chromosomes 7, and 17q. These losses and gains were also confirmed by other techniques, such as G-banding, SKY and FISH (Aldosari et al 2002;Avet-Loiseau et al 1999 ;Bayani et al 2000;Eberhart et al 2002;Gilhuis et al 2000). Array CGH of 47 MB (Speicher and Carter 2005) showed gain of 17q, 7, and 1q and loss of 17p, 11p,10q and 8.…”
Section: Chromosomal Aberration and Its Corroletion To Clinicohistopasupporting
confidence: 54%
“…To compare our ®ndings with those of previous investigations, we have reviewed genetic data from six genome-wide studies covering a total of 107 medulloblastomas (Blaeker et al, 1996;Reardon et al, 1997;Avet-Loiseau et al, 1999;Nicholson et al, 1999;Gilhuis et al, 2000;von Deimling et al, 2000). The summarized results revealed that deletions of 17p (39%), 10q (35%), 8p (32%), 11p (28%), 11q (28%), and 16q (20%) are the most frequent genetic abnormalities involving loss of genetic materials.…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 gene was found to be infrequently mutated in medulloblastoma, indicating that TP53 is not the target on 17p (Saylors et al, 1991). Using comparative genomic hybridization technique, several groups have demonstrated the involvement of multiple chromosomes in medulloblastoma (Avet-Loiseau et al, 1999;Gilhuis et al, 2000;Nicholson et al, 1999;Reardon et al, 1997). Of those chromosomes that show deletions, losses of chromosomes 10q and 8p are recurrent genetic alterations, with about 30% of tumors showing such abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Medulloblastoma, a representative malignant brain tumor, showed frequent disruption at chromosome 3p by a deletion mapping study, suggesting a novel tumor suppressor gene in this region (Avet-Loiseau et al, 1999;Bayani et al, 2000). Recently, hypermethylation of the RASSF1A promoter region in medulloblastoma has been reported (Harada et al, 2002;Lusher et al, 2002).…”
mentioning
confidence: 99%